Transmission Electron Microscopy A Textbook for Materials Science - Williams, David B.; Carter, C. Barry (Springer US : Imprint: Springer, 2009)
This groundbreaking text has been established as the market leader throughout the world. Now profusely illustrated with full color figures and diagrams throughout the text, Transmission Electron Microscopy: A Textbook for Materials Science, Second Edition, provides the necessary insight and guidance for successful hands-on application of this versatile and powerful materials characterization technique. For this first new edition in 12 years, many sections have been completely rewritten with all others revised and updated. The new edition also includes an extensive collection of questions for the student, providing approximately 800 for self-assessment and over 400 that are suitable for homework assignment. Key Features: Undisputed market leader, now completely revised and updated Ideal for use as a teaching text at the advanced undergraduate and graduate levels and as a hands-on reference for materials scientists Explains why a particular technique should be used and how a specific concept can be put into practice Nearly 700 figures and diagrams, most in full color Praise for the first edition: `The best textbook for this audience available.' - American Scientist "...highly readable, and an extremely valuable text for all users of the TEM at every level. Treat yourself to a copy!" - Microscopy and Microanalysis `This book is written in such a comprehensive manner that it is understandable to all people who are trained in physical science and it will be useful both for the expert as well as the student.' - Micron `The book answers nearly any question - be it instrumental, practical, or theoretical - either directly or with an appropriate reference...This book provides a basic, clear-cut presentation of how transmission electron microscopes should be used and of how this depends specifically on one's specific undergoing project.' - MRS Bulletin `The only complete text now available which includes all the remarkable advances made in the field of TEM in the past 30-40 years....The authors can be proud of an enormous task, very well done.' - from the Foreword by Professor Gareth Thomas, University of California, Berkeley.